Pengaruh Green Human Resource Management dan Green Organizational Culture terhadap Employee Green Behavior di InterContinental Bali Resort - Mawarni, Kadek Dwi Putri; Rastitiati, Ni Kade Juli (Program Studi Manajemen Divisi Kamar, 2025)
This study aims to determine the influence of green human resource management and green organizational culture on employee green behavior. The sampling method used was purposive sampling with 87 respondents who were employees of ABC Bali Resort. Data collection was carried out using a questionnaire that had been tested for validity and reliability. The data analysis techniques used in this study were multiple linear regression, t-test, F-test, correlation coefficient, and coefficient of determination. The result shows that green human resource management has a positive and significant effect on employee green behavior, green organizational culture has a positive and significant effect on employee green behavior, and green human resource management and green organizational culture simultaneously have a significant effect on employee green behavior. The coefficient of determination indicates that both independent variables are able to explain 62.3% of the variation in employee green behavior, while the remaining 37.7% is influenced by other factors not examined in this study. Based on the results of the study, it shows that employee participation in programs that support environmental sustainability is still low. In addition, resources in operations, electricity and water have not been used efficiently and sustainably.